2020
DOI: 10.1002/jcla.23454
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐148a‐3p inhibits cancer progression and is a novel screening biomarker for gastric cancer

Abstract: Purpose Dysregulation of miR‐148a‐3p in gastric cancer was reported. However, the diagnostic potential and biological function of miR‐148a‐3p in gastric cancer progression is not fully studied. Methods Bioinformatics analysis and RT‐qPCR assay were performed to analyze the expression of miR‐148a‐3p in gastric cancer tissues and plasma of gastric cancer patients. Receiver operating characteristic curve analysis was performed to analyze the diagnostic value of miR‐148a‐3p. In vitro proliferation, apoptosis, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…MiRNA expression profile is related to the characteristics of diverse cancers and can be used for screening differentially expressed miRNAs [22,23]. Through microarray analysis, we found that the expression of miR-4636, miR-1298, miR-4268, miR-4290, miR-1275, miR-148a-3p, miR-375, miR-943 and miR-665 were downregulated in GC tissues, which is consistent with the previous research findings [9,[24][25][26][27][28][29][30][31]. Herein, we mainly focused on miR-1269b.…”
Section: Discussionsupporting
confidence: 89%
“…MiRNA expression profile is related to the characteristics of diverse cancers and can be used for screening differentially expressed miRNAs [22,23]. Through microarray analysis, we found that the expression of miR-4636, miR-1298, miR-4268, miR-4290, miR-1275, miR-148a-3p, miR-375, miR-943 and miR-665 were downregulated in GC tissues, which is consistent with the previous research findings [9,[24][25][26][27][28][29][30][31]. Herein, we mainly focused on miR-1269b.…”
Section: Discussionsupporting
confidence: 89%
“…The proliferation of bone marrow mesenchymal stem cell and non-smallcell lung cancer can also be promoted by miR-148a-3p mimic [41,42] which consistent with our present research. However, Bao et al and Wang et al have reported that overexpression of miR-148a-3p inhibited the proliferation of gastric cancer cells [43] and diabetic retinopathy cell model [44], respectively. Therefore, miR-148a-3p displays inconsistent effects in the proliferation of different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have also explored the role of miRNAs in GCs including miR‐148a‐3p 40 and miR‐212. 41 Bao et al investigated the diagnostic potential and biological function of miR‐148a‐3p in GC progression in the GC tissues and plasma of patients and found that miR‐148a‐3p was significantly downregulated in both the gastric tissue and plasma of GC patients, suggesting that miR‐148a‐3p may inhibit cancer progression and is a novel diagnostic biomarker for GC.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Bao et al investigated the diagnostic potential and biological function of miR‐148a‐3p in GC progression in the GC tissues and plasma of patients and found that miR‐148a‐3p was significantly downregulated in both the gastric tissue and plasma of GC patients, suggesting that miR‐148a‐3p may inhibit cancer progression and is a novel diagnostic biomarker for GC. 40 Shao et al 41 analyzed the relationship of serum level of miR‐212 with GC through detecting the serum level of miR‐212 in 100 healthy people and 110 GC patients, and these authors found that miR‐212 was epigenetically downregulated in GC and could directly regulate the 3′UTR of SOX4 mRNA to suppress p53 and Bax, suggesting that low level of miR‐212 can be a potential circulation biomarker and poor prognosis predicator of GC. Novel findings in our study and in other studies 40 , 41 will ultimately accumulate to clarify the mechanism of GC and clear the way for better treatment of this cancer.…”
Section: Discussionmentioning
confidence: 99%